The Influence of Work Environment, Work Culture and Job Satisfaction on Employee Loyalty - Sjarifudin, Didin; Widyastuti, Tri; Renwarin, Joseph MJ; Suroso, Sugeng (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Research on the influence of the work environment, work culture and job satisfaction on employee loyalty is a literature review research article. The purpose of writing this article is to build a research hypothesis on the influence between variables, which will later be used in further research, within the scope of human resource management. The article writing method is the library research method, which is sourced from online media such as Google Scholar, Garba Reference Digital, Sinta Journal, and DOAJ. Where this research is based on the results of previous research, thereby producing a research hypothesis. The results of this literature review research are as follows: 1) The work environment influences employee loyalty; 2) Work culture influences employee loyalty; and 3) Job satisfaction influences employee loyalty. The purpose of writing this literature review article is to build a research hypothesis on the influence between variables. Methodology/approach – The method for writing literature review articles is the qualitative library research method, which is sourced from online media such as Google Scholar, Digital Reference Garba, Sinta Journal, and DOAJ. The findings and the results of this literature review research are as follows: 1) The work environment influences employee loyalty; 2) Work culture influences employee loyalty; and 3) Job satisfaction influences employee loyalty.